Local Scour at Triangular Labyrinth Side Weirs Located on an Alluvial Channel - Tunc, Mustafa; Emiroglu, Muhammet Emin; Gogus, Mustafa (Asce-Amer Soc Civil Engineers, 2022)
The studies on labyrinth side weirs have received considerable attention in existing literature. A mobile bed, which causes significant morphological bed changes, can be induced by the side overflow weir. In this study, the local scour depths that occur near a triangular labyrinth side weir at a 90 degrees angle in a straight channel with an alluvial bed were experimentally examined under steady flow conditions with free overflow of the weir. Based on a dimensional analysis applied according to the parameters of the study, it was determined that dimensionless equilibrium scour depth is dependent on the approach flow intensity, dimensionless side weir crest height, dimensionless median grain size, dimensionless side weir opening, and dimensionless volumetric amount of upstream sediment feed under live-bed scour conditions. For different combinations of weir opening length and weir height, data for a set of 81 runs were obtained. The results show that an increase in weir crest height results in a decrease in dimensionless maximum scour depth. In the clear-water scour experiments, sediment deposits were observed downstream of the weir. In the live-bed scour experiments, the dimensions of the scours and sediment deposits that occurred upstream and downstream of the weir exhibited periodic changes. Good consistency was attained in the developed empirical equations between the calculated and measured values of the equilibrium scour depth.
Keywords: Labyrinth side weir; Local scour; Clear-water scour; Live-bed scour; Flow intensity; Alluvial channel